2019
DOI: 10.4149/bll_2019_136
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 mediated JAK/STAT3 signaling pathway in cancer patients with cachexia

Abstract: OBJECTIVES: We investigated the changes in the IL-6 and STAT3 expression levels in cachectic and noncachectic patients with gastric, lung and breast cancer and evaluated the association between IL-6 and STAT3 levels and cancer types in terms of cachexia condition. BACKGROUND: Cancer-associated cachexia, observed in nearly 50-80 % of cancer patients, has drawn attention in advanced patients. IL-6/JAK/STAT pathway plays an essential role in the progression of cancer cachexia through the regulation of the infl am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 44 publications
(59 reference statements)
1
26
0
Order By: Relevance
“…IL-6. Numerous proinflammatory factors have been discovered to serve important roles in the muscle atrophy caused by cancer cachexia (13,29,60,61). il-6 is produced by macrophages (62) and fibroblasts (63) and was also found to be secreted by tumor cells (64).…”
Section: Induction Of Proinflammatory Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…IL-6. Numerous proinflammatory factors have been discovered to serve important roles in the muscle atrophy caused by cancer cachexia (13,29,60,61). il-6 is produced by macrophages (62) and fibroblasts (63) and was also found to be secreted by tumor cells (64).…”
Section: Induction Of Proinflammatory Factorsmentioning
confidence: 99%
“…clinical studies have also revealed that compared with healthy controls, patients with non-small cell lc (nSclc) with cachexia had smaller muscle fiber cross-sectional areas and significantly increased plasma il-6 levels (68). The il-6/Janus kinase (JaK)/STaT3 signaling pathway was discovered to have an essential role in the progression of cancer cachexia by regulating the inflammatory response (13,60). Pin et al (61) intraperitoneally injected eS-2 human ovarian cancer cells into nod-Scidγ mice to establish a cancer cachexia model; the experimental studies revealed significantly upregulated IL-6 and phosphorylated STaT3 levels in the plasma and ascites of model mice compared with control mice.…”
Section: Induction Of Proinflammatory Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…N-ratio staging system -the staging system based on the metastatic lymph node ratio between metastatic and examined lymph nodes (N-ratio) in gastric cancer patients (2,5,7,8,10,11).…”
Section: Tnm Staging System (Tnm)mentioning
confidence: 99%
“…The resulting cytokines participate in the pathways activating the processes related to the destruction of muscle fibers as well as the reduction of adipose tissue [ 8 ]. IL-6 participates in the development of inflammation in the course of many cancers: breast, prostate, colon, lung, stomach and brain [ 11 ]. The overproduction of IL-6 contributes to the promotion of processes conducive to the breakdown of muscle tissue (attempts have been made to use this parameter to monitor the nutritional status of the patient), but it is worth noting that in some cases, cachexia may develop without a marked increase in typical pro-inflammatory cytokines (including IL-6) [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%